Khoris oikountes and the obligations of freedmen in late classical and early hellenistic Athens - Lewis, David; Canevaro, Mirko (Luciano Editore, 2014)
This article addresses the riddle of the identity of the khoris oikountes or 'dwellers apart' mentioned by Demosthenes (4.36-7) as a group subject to the navy draft. Many scholars view the term as a designation for slaves who lived separately from their owners; others argue that khoris oikountes was a general term for freed slaves. We show that two groups of freedmen existed in Athenian law, one bound to remain in their ex-owner's household and subject to post-manumission obligations, the other not. It is the latter group, which occupied a position vis-a-vis the state almost identical to that of metics, which is the most credible candidate for identification with Demosthenes' khoris oikountes. Included is an in-depth philological and historical analysis of the 'wills of the philosophers' in Diogenes Laertius.